Lightning safety of under-privileged communities around Lake Victoria - Gomes, Chandima; Mary, Ahurra Kulyaka (Taylor and Francis, 2015)
This is one of the first studies on lightning incidents that take place in the neighbourhood of Lake Victoria, the largest tropical lake in the world that borders Uganda, Tanzania and Kenya. Lightning accident statistics in the region have been documented segment wise. The number of lightning occurrences in the north-western shore and that in the north-eastern shore were compared. The region has a distinctly recognizable season with high lightning accident density which runs from May to November and low lightning accident period from December to April. August peaks in lightning incidents. Lightning-related incidents are very much prevalent during the period between May and August due to the dominant south easterlies. The study reveals that the north-western part has slightly higher lightning accidents than the north-eastern part. North-eastern part records relatively high number of lightning accidents in the morning hours whereas the north-western sector experiences the same in the afternoon hours. Many features of lightning accidents and their locations have features that are in agreement with the same observed in other parts of East Africa. Following the statistics collected and incidents observed, suitable safety measures have been recommended for the communities that reside in the shores and nearby areas of Lake Victoria.